Reconciliation in wolves (Canis lupus): new evidence for a comparative perspective - Cordoni G.; PALAGI, ELISABETTA (Ethology, 2008)
Social animals gain benefits from cooperative behaviours. However, social systems also imply competition and conflict of interest. To cope with dispersal forces, group-living animals use several peace-keeping tactics, which have been deeply investigated in primates. Other taxa, however, have been often neglected in this field research. Wolves (Canis lupus) with their high sociality and cooperative behaviour may be a good model species to investigate the reconciliation process. In this study, we provide the first evidence for the occurrence of reconciliation in a group of zoo-kept wolves. The conciliatory contacts were uniformly distributed across the different sex-class combinations. We found a linear dominance hierarchy in the colony under study, although the hierarchical relationships did not seem to affect the reconciliation dynamics. Moreover, both aggressors and victims initiated first post-conflict affinitive contact with comparable rates and both high- and low-intensity conflicts were reconciled with similar percentages. Finally, we found that coalitionary support may be a good predictor for high level of conciliatory contacts in this species.